A Description of the Vascular Anatomy of the Tensor Fascia Lata Perforator Flap Using Computed Tomography Angiography. (June 2018) - Powers, Jeremy M.; Martinez, Mariana; Zhang, Shuhao; Kale, Santosh S.
Abstract : Background: The perforator anatomy of the tensor fascia lata (TFL) flap has been studied using cadaver dissection; however, exact descriptions of location, size, and origin of perforator vessels using preoperative imaging modalities remain limited. The aims of this study are to describe TFL perforator anatomy using high-resolution computed tomography angiography (CTA) and to correlate these findings with landmarks for the anterolateral thigh flap to facilitate flap planning. Methods: We identified 33 patients who previously underwent bilateral lower extremity CTAs for preoperative planning of free-flap reconstruction. The images were retrospectively reviewed, and the TFL perforator number, size, type, location, and overall pedicle origin and length were recorded. Results: Thirty-three patients and 59 thighs were included in the study. There was an average of 2.5 perforators per TFL. All perforators arose from the ascending branch of the lateral circumflex femoral artery with an average pedicle length of 8.3 cm (range, 6.0–11.2 cm). Sixty-six percent of perforators were septocutaneous and 34% were musculocutaneous. The average perforator size as measured on CTA was 3 mm. The average perforator location was 10.1 cm inferior and 8.5 cm lateral to the line drawn from the anterior superior iliac spine to the superolateral patella. Conclusions: To our knowledge, this is the first study to characterize the vascular anatomy of the TFL perforator flap using high-resolution CTA and correlate this with well-established landmarks used in the planning for other thigh-based flaps. We believe data will facilitate flap design and dissection; potentially shortening operating room times, limiting exploratory incisions used to confirm the presence of thigh based perforators, and improving overall outcomes for patients.